Blockchain Security as “People Security”: Applying Sociotechnical Security to Blockchain Technology - Nabben, Kelsie (Frontiers in Computer Science, 2021)
The notion that blockchains offer decentralized, “trustless” guarantees of security through technology is a fundamental misconception held by many advocates. This misconception hampers participants from understanding the security differences between public and private blockchains and adopting blockchain technology in suitable contexts. This paper introduces the notion of “people security” to argue that blockchains hold inherent limitations in offering accurate security guarantees to people as participants in blockchain-based infrastructure, due to the differing nature of the threats to participants reliant on blockchain as secure digital infrastructure, as well as the technical limitations between different types of blockchain architecture. This paper applies a sociotechnical security framework to assess the social, software, and infrastructural layers of blockchain applications to reconceptualize “blockchain security” as “people security.” A sociotechnical security analysis of existing macrosocial level blockchain systems surfaces discrepancies between the social, technical, and infrastructural layers of a blockchain network, the technical and governance decisions that characterize the network, and the expectations of, and threats to, participants using the network. The results identify a number of security and trust assumptions against various blockchain architectures, participants, and applications. Findings indicate that private blockchains have serious limitations for securing the interests of users in macrosocial contexts, due to their centralized nature. In contrast, public blockchains reveal trust and security shortcomings at the micro and meso-organizational levels, yet there is a lack of suitable desktop case studies by which to analyze sociotechnical security at the macrosocial level. These assumptions need to be further investigated and addressed in order for blockchain security to more accurately provide “people security”.